2022
DOI: 10.1186/s12954-022-00688-4
|View full text |Cite
|
Sign up to set email alerts
|

‘It’s the same thing as giving them CPR training’: rural first responders’ perspectives on naloxone

Abstract: The Substance Abuse and Mental Health Services Administration’s (SAMHSA) Harm Reduction grant program expanded access to several harm reduction strategies to mitigate opioid overdose fatalities, including expanding access to naloxone. Interviews with first responders in a frontier and remote (FAR) state were conducted to understand their job responsibilities in relation to overdose response and prevention and their perceptions of training laypersons to administer naloxone. This study includes 22 interviews wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 67 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…Evidence suggests that misperceptions about overdose and naloxone, as well as stigmatizing beliefs about people who use drugs, may affect both layperson and first responder willingness and interest in carrying and using naloxone [29][30][31][32][33]; for example, first responders may be ambivalent about "providing naloxone to those they deem undeserving" [34], and a review found that stigmatizing attitudes among first responders may reduce the likelihood of bystander response [35]. Some first responders have noted that laypersons in their communities may fear "real and perceived cultural opposition" to harm reduction strategies [36]. Such reticence and stigma may even persist after OEND training [29,37] and have been described as fundamentally hindering the US response to the opioid overdose crisis [38].…”
Section: Misperceptions About Naloxone and Overdose May Inhibit Oend ...mentioning
confidence: 99%
“…Evidence suggests that misperceptions about overdose and naloxone, as well as stigmatizing beliefs about people who use drugs, may affect both layperson and first responder willingness and interest in carrying and using naloxone [29][30][31][32][33]; for example, first responders may be ambivalent about "providing naloxone to those they deem undeserving" [34], and a review found that stigmatizing attitudes among first responders may reduce the likelihood of bystander response [35]. Some first responders have noted that laypersons in their communities may fear "real and perceived cultural opposition" to harm reduction strategies [36]. Such reticence and stigma may even persist after OEND training [29,37] and have been described as fundamentally hindering the US response to the opioid overdose crisis [38].…”
Section: Misperceptions About Naloxone and Overdose May Inhibit Oend ...mentioning
confidence: 99%